Facile synthesis of CdTe-based quantum dots promoted by mercaptosuccinic acid and hydrazine. (2nd June 2015) - Tan, Jiawei; Liang, Yan; Wang, Jiexin; Chen, Jianfeng; Sun, Baochang; Shao, Lei
<x xml:space="preserve">Abstract</x> High-quality CdTe and CdSexTe1−x QDs were prepared at 95 °C within 45 minutes with the sizes controlled by N2H4 concentration.